Prevalence of gynaecological disease in women with an HMLH1 mutation in the Northern Cape province: Survey of a population with Lynch Syndrome in South Africa - Lerm, Marlize (Department of Obstetrics and Gynaecology, 2017)
Objective: Lynch syndrome, previously called hereditary non-polyposis colorectal cancer (HNPCC), is one of the most common hereditary cancer syndromes with an association with gynaecological cancers. Members of affected families have an increased risk for colon cancer as well as extra colonic sites; in particular endometrial and ovarian cancer. A cohort of patients with Lynch syndrome in the Northern Cape, South Africa has been identified and followed up. According to recommendations by the International Collaborative Group on HNPCC (ICGHNPCC); women affected with the gene mutation warrant full gynaecological assessment to exclude endometrial and ovarian cancer. Thus far the recommended screening has not been possible and the apparent prevalence of gynaecological cancer or premalignancies among this high risk group has not been established. The aim of this study was to determine the actual apparent prevalence of gynaecological pathology in this cohort of patients; by way of screening. Methods: Women with a known gene mutation, or close relatives of affected family members, utilising the annual colorectal service in the Northern Cape, who fulfilled the inclusion criteria, were recruited to undergo gynaecological evaluation. The participants had a gynaecological examination which included a Papanicolaou smear, a pelvic ultrasound and endometrial sampling. The resultant data was captured on an Excel spread sheet and a descriptive analysis was done. Results: In total 43 women were recruited, of which 18 were postmenopausal and 25 premenopausal. 35 of these women had a known hMLH1 gene mutation. The eight remaining women had either normal genotyping (n=7) or were awaiting molecular test results (n=1). Only twenty-one of these participants agreed to endometrial sampling, in addition to pelvic ultrasound and gynaecological examination. Histological results were therefore available for the 21 participants. One patient was diagnosed with a grade-2 endometroid adenocarcinoma. No cases of endometrial hyperplasia were found. Thirty pelvic ultrasound scans were performed. Of these, one patient had an enlarged adnexal mass. No cervical premalignancies were diagnosed on cervical smears, with one abnormal smear of atypical cells of unknown significance (ASCUS) diagnosed. Conclusion: The apparent prevalence of gynaecological disease in this study population was lower than expected. We conclude however that this high risk group of women should still undergo regular gynaecological screening which should include history taking and clinical examination. Screening using routine endometrial sampling and pelvic ultrasound in asymptomatic women did not appear to be beneficial.